2004
DOI: 10.3171/jns.2004.100.5.0813
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cancer-specific anterior skull base quality-of-life questionnaire

Abstract: The proposed questionnaire appears to be sufficiently reliable and valid in estimating a patient's QOL after extirpation of anterior skull base tumors. The instrument can be used in face-to-face interviews and via electronic or regular mail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
116
1
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 29 publications
2
116
1
6
Order By: Relevance
“…17 The α score varies from 0 to 1 and a score of 0.70 or higher is considered to be predictive of the reliability of the questionnaire. 2 In this study, we found α-Cornbach values of 0.69 to 1 with most values being !0.75 for each domain, suggesting a good reliability of the ASBS-Q instrument in studying patients undergoing endoscopic skull base surgery. Our study involves a group of patients operated by the same group of surgeons.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…17 The α score varies from 0 to 1 and a score of 0.70 or higher is considered to be predictive of the reliability of the questionnaire. 2 In this study, we found α-Cornbach values of 0.69 to 1 with most values being !0.75 for each domain, suggesting a good reliability of the ASBS-Q instrument in studying patients undergoing endoscopic skull base surgery. Our study involves a group of patients operated by the same group of surgeons.…”
Section: Discussionmentioning
confidence: 78%
“…2,9 Six relevant domains were identified by factor analysis: role of performance, physical function, vitality, pain, specific symptoms, and impact upon emotions. Internal consistency of each of the six domains was evaluated using Cronbach's α coefficient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASBQ was subsequently demonstrated to have psychometric validity for site-specific QOL assessment following anterior skull base surgery for both transcranial and endoscopic approaches. 4,17 A prospective study of QOL in patients undergoing open anterior skull base surgery has only recently been described. Abergel et al assessed a series of 39 patients with the ASBQ prior to surgery and again at 2 postoperative points.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used the multidimensional diseasespecific questionnaire for anterior skull base neoplasms developed by Gil and associates to estimate the effect of the endonasal surgical approach for various cranial base lesions on patients' QOL. 9 A higher score in the QOL questionnaire indicates a good outcome, with a minimum score of 1.0 and a maximum score of 5.0.…”
Section: Methodsmentioning
confidence: 99%